KAJIAN INTERAKSI OBAT PASIEN DIABETES MELITUS TIPE 2 DENGAN KOMORBID HIPERTENSI RAWAT JALAN DI RUMAH SAKIT AREA KOTA YOGYAKARTA - Ginanjar Zukhruf Saputri; Siti Anisya Rahayu; Endang Darmawan; Prita Anggraini Kartika Sari; Woro Supadmi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Patients with type 2 diabetes mellitus and hypertension comorbidity generally receive more than one medication, increasing the risk of drug interactions that may affect therapeutic outcomes. This study aimed to determine the potential drug interactions in outpatients with type 2 diabetes mellitus and hypertension at PKU Muhammadiyah Gamping Hospital during January–December 2024. This research employed a descriptive-retrospective observational method using 44 medical records selected through purposive sampling based on inclusion and exclusion criteria. Drug interactions were assessed using the MedFacts Pocket Guide of Drug Interactions, Stockley’s Drug Interactions (2009), and drug interaction checkers from Medscape and Drugs.com based on interaction mechanisms and severity levels. The results showed 129 cases of drug interactions, with the most common combination being metformin–amlodipine (10 cases; 7.7%). The most frequent interaction mechanism was pharmacodynamic interaction (68 cases; 52.71%), while the severity level was predominantly moderate according to Medscape (65 cases; 50.38%) and Drugs.com (79 cases; 61.24%). Major interactions were identified in the bisoprolol fumarate–clonidine combination (4 cases; 5.3%). This study indicates the potential for drug interactions in antidiabetic and antihypertensive therapy, highlighting the need for therapeutic monitoring and dose adjustment to improve treatment safety and effectiveness.